Constructing the Suspicious: Data Production, Circulation, and Interpretation by DHS Fusion Centers. (August 2015) - Regan, Priscilla M.; Monahan, Torin; Craven, Krista
Suspicious activity reports (SARs) are an increasingly important tool in the law-enforcement repertoire, especially for counterterrorism. In spite of significant problems with such reports, they are experiencing a resurgence that can be attributed partly to the institutionalization of Department of Homeland Security (DHS) "fusion centers, " which are taking the lead in vetting and interpreting these reports as they enter into law-enforcement and counterterrorism databases. Based on a 3-year study of DHS fusion centers, this article reviews a range of problems with SARs and argues that robust community relationships are necessary to achieve contextually situated reports that eschew overt forms of bias.